D’VEG – marketplace de produtos veganos - Lombardo, Bruna Carioni (2023)
The purpose of this project is to develop a marketplace to fix the accessibility, reliability, and distribution problems in the vegan market. The platform aims to unite quality and variety, with more conscious and ecological consumption. Based on the research, it was validated this is a viable market, with the objective in supplying a higher number of people with vegan products, fostering the creation of a comunity through an enjoyable and sustainable purchase experience